EVALUASI KINERJA TATA KELOLA CURUG CIBEREUM BERBASIS INDIKATOR-INDIKATOR SAPTA PESONA - Fongnawati Budhijono; Sugiarto Sugiarto; Januar Wahjudi; Sutrisno Sutrisno; Muhammad Fuad (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The contribution of the tourism industry to the Indonesian economy is increasingly being taken into account. Agrotourism has the potential to contribute significantly in advancing Indonesian tourism. Indonesia's agro-tourism potential is huge due to it being supported by the richness and diversity of agriculture, fisheries, plantations, animal husbandry, and forestry. This research was conducted at Cibereum Waterfall located in the Gede Pangrango National Park area, West Java, Indonesia. This study aims to examine the governance performance of CibereumWaterfall in relation to the indicators of Sapta Pesona (tourism seven charms).The novelty of this research is to formulate Sapta Pesona indicators of Cibereum Waterfall. This study used a mixed research method QUAN+ qual. Data were taken using multistage sampling with the Concurrent Triangulation Strategy, involving 560 research respondents and 16 informants. By using Performance – Importance analysis the research found that there are 11 indicators of Sapta Pesona that require immediate improvement. The performance of Safe, Memories, Friendly and Clean elements of Sapta Pesona must be further improved to answer the needs of tourists. The functions of governance that still need attention to improve are Supervision, Managerial, Compliance and Monitoring.